Protocol for preparing SUV420H1 in complex with the nucleosome containing H2A.Z and H4K20Ecx for structure determination - Li Huang; Zheng Zhou (STAR Protocols, 2024)
Summary: The histone lysine methyltransferase SUV420H1 preferentially targets the H2A.Z-containing nucleosome core particle (H2A.Z-NCP) and catalyzes the H4K20me2 modification at replication origins. Here, we present a protocol for preparing SUV420H1 in complex with the nucleosome containing H2A.Z and H4K20Ecx for structure determination. We describe steps for the installation of S-ethyl-cysteine (Ecx), nucleosome and complex preparation, and performing the cryoelectron microscopy (cryo-EM) sample check. This protocol substitutes lysine 20 in histone H4 with S-ethyl-cysteine (H4K20Ecx), which enhances the stability of the interaction between SUV420H1 and nucleosomes.For complete details on the use and execution of this protocol, please refer to Huang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.